Immunogenicity and Protective Potential of Mucosal Vaccine Formulations Based on Conserved Epitopes of Influenza A Viruses Fused to an Innovative Ring Nanoplatform in Mice and Chickens - Calzas, Cynthia; Mao, Molida; Turpaud, Mathilde; Viboud, Quentin; Mettier, Joelle; Figueroa, Thomas; Bessière, Pierre; Mangin, Antoine; Sedano, Laura; Hervé, Pierre-Louis; Volmer, Romain; Ducatez, Mariette F.; et al. (Frontiers in Immunology, 2021)
Current inactivated vaccines against influenza A viruses (IAV) mainly induce immune responses against highly variable epitopes across strains and are mostly delivered parenterally, limiting the development of an effective mucosal immunity. In this study, we evaluated the potential of intranasal formulations incorporating conserved IAV epitopes, namely the long alpha helix (LAH) of the stalk domain of hemagglutinin and three tandem repeats of the ectodomain of the matrix protein 2 (3M2e), as universal mucosal anti-IAV vaccines in mice and chickens. The IAV epitopes were grafted to nanorings, a novel platform technology for mucosal vaccination formed by the nucleoprotein (N) of the respiratory syncytial virus, in fusion or not with the C-terminal end of the P97 protein (P97c), a recently identified Toll-like receptor 5 agonist. Fusion of LAH to nanorings boosted the generation of LAH-specific systemic and local antibody responses as well as cellular immunity in mice, whereas the carrier effect of nanorings was less pronounced towards 3M2e. Mice vaccinated with chimeric nanorings bearing IAV epitopes in fusion with P97c presented modest LAH- or M2e-specific IgG titers in serum and were unable to generate a mucosal humoral response. In contrast, N-3M2e or N-LAH nanorings admixed with MontanideTM gel (MG) triggered strong specific humoral responses, composed of serum type 1/type 2 IgG and mucosal IgG and IgA, as well as cellular responses dominated by type 1/type 17 cytokine profiles. All mice vaccinated with the [N-3M2e + N-LAH + MG] formulation survived an H1N1 challenge and the combination of both N-3M2e and N-LAH nanorings with MG enhanced the clinical and/or virological protective potential of the preparation in comparison to individual nanorings. Chickens vaccinated parenterally or mucosally with N-LAH and N-3M2e nanorings admixed with MontanideTM adjuvants developed a specific systemic humoral response, which nonetheless failed to confer protection against heterosubtypic challenge with a highly pathogenic H5N8 strain. Thus, while the combination of N-LAH and N-3M2e nanorings with MontanideTM adjuvants shows promise as a universal mucosal anti-IAV vaccine in the mouse model, further experiments have to be conducted to extend its efficacy to poultry.